Obtenção de compósitos MoS2 / MoO3 aplicados na remoção de compostos catiônicos via adsorção - Souza, Thais Mota de (2022)
Sanitation is a practice applied in society since antiquity in order to promote the maintenance of public health in addition to protecting the environment. Purification of water for public supply is one of the operations within the sanitation cycle, basically composed of physical and chemical steps that promote the removal of impurities from the water. In this sense, the treatment currently used demonstrates a deficiency in the removal of so-called emerging contaminants such as hormones, drugs, metals, among others. Thus, in this work, a study was carried out on the adsorption capacity of the composite material MoS2/MoS3 obtained from a heat treatment (roasting) performed on the MoS2 precursor matrix with the purpose of removing cations. Samples of the precursor material were thermally analyzed using TG/DTG and DSC techniques and through these results, the first calcination condition was established, at 300 ºC for 150 min. Starting from this point, a 2k factorial design with central point was applied. The crystalline phase and the structural properties of the samples were characterized by X-ray diffractometry (XRD) and Raman spectroscopy, from which the occurrence of a mixture between 2h-MoS2 and α-MoO3 was verified; Fourier transform infrared spectroscopy (FTIR) indicated the surface formation of MoO3 structures at lower treatment temperatures. Through the micrographs obtained by scanning electron microscopy with an MEV-FEG field emission source, it was possible to visualize the morphological changes that occurred in the samples caused by the heat treatment, a treatment that directly influenced the specific surface area of the samples, according to the adsorption analysis of N2 and BET. Kinetic adsorption tests were performed using the Methylene Blue (MB) dye, which demonstrated a high capacity of dye removal by materials with phase mixture. The presence of sites with sulfur (S) of the 2h-MoS2 phase favors the adsorption process and the presence of the orthorhombic phase of MoS3 allows the dispersion of this material in aqueous solution, thus enabling a greater adsorption capacity. Finally, adsorption isotherm tests allowed us to determine that the adsorption is favorable, and the adsorption isotherm model that fits is the Langmuir model, allowing to obtain the maximum adsorption capacity of the samples, with the one with the highest performance being capacity of 286.53 mg/g.